2017
DOI: 10.1080/23761407.2017.1335631
|View full text |Cite
|
Sign up to set email alerts
|

Culturally-Informed Interventions for Substance Abuse Among Indigenous Youth in the United States: A Review

Abstract: There is a current gap in research on culturally-informed substance abuse interventions for Indigenous youth, which this review begins to address. Promising areas of future research and interventions include bringing communities and families into treatment and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Surprisingly, it did not appear that conversations about teen substance use were routinely linked to risky sexual behavior. Both the focus group and KII interviewees seemed to compartmentalize these two behaviors, similar to previous prevention efforts with AIAN teens, which target either substance use [50,51,52,53,54,55,56,57] or contraception/sexual activity [58,59,60,61,62,63] separately; this is problematic as alcohol consumption can have an impact on the consistency of birth control utilization [64]. Therefore, studies on preconception health, like CHAT and others, are important in altering the community’s perception of how to prevent AEP and FASD by focusing on the dual-behavioral approach prior to pregnancy.…”
Section: Discussionmentioning
confidence: 64%
“…Surprisingly, it did not appear that conversations about teen substance use were routinely linked to risky sexual behavior. Both the focus group and KII interviewees seemed to compartmentalize these two behaviors, similar to previous prevention efforts with AIAN teens, which target either substance use [50,51,52,53,54,55,56,57] or contraception/sexual activity [58,59,60,61,62,63] separately; this is problematic as alcohol consumption can have an impact on the consistency of birth control utilization [64]. Therefore, studies on preconception health, like CHAT and others, are important in altering the community’s perception of how to prevent AEP and FASD by focusing on the dual-behavioral approach prior to pregnancy.…”
Section: Discussionmentioning
confidence: 64%
“…This is particularly true given the mindset of many prevention programs with AI/AN adolescents, which often compartmentalizes behavioral change. For example, many previous prevention efforts with AI/AN teens targeted either substance use (Allen et al, 2014, Dickerson et al, 2016, Donovan et al, 2015, Gilder et al, 2017, Komro et al, 2017, Kulis et al, 2017, Liddell and Burnette, 2017, Philip et al, 2016 or contraception/sexual activity (Garwick et al, 2008, Hohman-Billmeier et al, 2016, Kenyon et al, 2019, Schanen et al, 2017, Shegog et al, 2017, Tingey et al, 2017 separately, which is problematic as alcohol consumption can have an impact on the consistency of birth control utilization (Campo et al, 2010). Other researchers conclude that interventions addressing both substance use and sexual risk-taking behaviors, such as the CHOICES/CHAT interventions, are essential to reduce risk for AEP (Chambers et al, 2016, Markham et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic literature review of substance abuse prevention curricula for indigenous youth identified a total of 14 empirical studies published between 1988 and 2016 (Liddell & Burnette, 2017). Of the studies identified by Liddell and Burnette, only five (36%) examined substance use behavioral outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%